Mastering Software Quality Engineering: A Holistic Approach - PERLA, SRIKANTH (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2015)
Software quality engineering (SQE) is essential for ensuring that software applications meet the required standards of functionality, performance, security, and reliability. As software development methodologies evolve, the need for a comprehensive, holistic approach to software quality has become more critical. This paper explores the concept of mastering software quality engineering through a unified, multi-disciplinary approach. It highlights the integration of various techniques, such as test automation, continuous integration (CI), continuous delivery (CD), and defect management, to create a seamless workflow that drives software quality. The research also emphasizes the importance of collaboration between development, testing, and operations teams in achieving optimal software quality. This holistic approach leverages both traditional and modern practices, including agile development and DevOps, to ensure that software is developed, tested, and deployed effectively. The study investigates the tools, methodologies, and frameworks used to implement this approach, along with challenges faced by organizations in achieving high software quality standards. Additionally, the paper presents case studies and performance metrics to demonstrate the effectiveness of a holistic approach to software quality engineering. By addressing the challenges in quality assurance and introducing strategies for overcoming them, this paper provides valuable insights into mastering SQE for modern software development environments.